2012
DOI: 10.1088/1751-8113/45/11/115307
|View full text |Cite
|
Sign up to set email alerts
|

A new simple class of superpotentials in SUSY quantum mechanics

Abstract: In this work we introduce the class of quantum mechanics superpotentials W (x) = gε(x)x 2n and study in details the cases n = 0 and 1. The n = 0 superpotential is shown to lead to the known problem of two supersymmetrically related Dirac delta potentials (well and barrier). The n = 1 case result in the potentialsFor V − we present the exact ground state solution and study the excited states by a variational technic. Starting from the ground state of V − and using logarithmic perturbation theory we study the gr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
21
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 24 publications
(48 reference statements)
5
21
2
Order By: Relevance
“…However, we are not aware of any proof that either of the basis sets (3) or (4) is complete. We see that present results are smaller, and therefore more accurate, than those of Marques et al [1]. In addition, the results in their tables 1 and 2 exhibit unchanged entries when the size of the basis set increases from to + 1 which reflects the fact that the added basis function improves the even (odd) state but has no effect on the odd (even) one.…”
Section: Susy Partnerscontrasting
confidence: 55%
See 4 more Smart Citations
“…However, we are not aware of any proof that either of the basis sets (3) or (4) is complete. We see that present results are smaller, and therefore more accurate, than those of Marques et al [1]. In addition, the results in their tables 1 and 2 exhibit unchanged entries when the size of the basis set increases from to + 1 which reflects the fact that the added basis function improves the even (odd) state but has no effect on the odd (even) one.…”
Section: Susy Partnerscontrasting
confidence: 55%
“…In a recent paper Marques et al [1] derived two new simple supersymmetric partner potentials and showed that the ground-state eigenfunction of one of the Hamiltonian operators can be obtained exactly. In order to calculate the remaining states they resorted to the Rayleigh-Ritz variational method.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations